2017
DOI: 10.1002/smll.201702474
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3D Graphene‐Oxide Spheres and Their Derived Hierarchical Porous Structures for High Performance Supercapacitors

Abstract: Graphene‐oxide (GO) based porous structures are highly desirable for supercapacitors, as the charge storage and transfer can be enhanced by advancement in the synthesis. An effective route is presented of, first, synthesis of three‐dimensional (3D) assembly of GO sheets in a spherical architecture (GOS) by flash‐freezing of GO dispersion, and then development of hierarchical porous graphene (HPG) networks by facile thermal‐shock reduction of GOS. This leads to a superior gravimetric specific capacitance of ≈30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…[29][30][31][38][39][40][41][42][43] For instance, Zhong et al reported a nitrogen-doped carbon system by carbonization of ZIF-8/GO at 950 C. 29 It is worth noting that the precursors exhibit a signicant mass loss with a catalyst yield of less than 30 wt%. 29 Since the MOFs/ZIFs can be calcined at as low as 350 C in ambient air, the high concentration of thermally decomposed oxygen functional groups (CO/CO 2 /H 2 O) from GO can cause signicant gasication of the ZIF ligand, in the form of CO/CO 2 , [44][45][46] at the expense of the mass yield of the catalyst. Furthermore, owing to the low specic surface area of GO (less than 100 m 2 g À1 ), 44 with its packed layer-structure, it is difficult to achieve a homogeneous hybrid system from the surface grown MOF/ZIF crystals.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[29][30][31][38][39][40][41][42][43] For instance, Zhong et al reported a nitrogen-doped carbon system by carbonization of ZIF-8/GO at 950 C. 29 It is worth noting that the precursors exhibit a signicant mass loss with a catalyst yield of less than 30 wt%. 29 Since the MOFs/ZIFs can be calcined at as low as 350 C in ambient air, the high concentration of thermally decomposed oxygen functional groups (CO/CO 2 /H 2 O) from GO can cause signicant gasication of the ZIF ligand, in the form of CO/CO 2 , [44][45][46] at the expense of the mass yield of the catalyst. Furthermore, owing to the low specic surface area of GO (less than 100 m 2 g À1 ), 44 with its packed layer-structure, it is difficult to achieve a homogeneous hybrid system from the surface grown MOF/ZIF crystals.…”
mentioning
confidence: 99%
“…29 Since the MOFs/ZIFs can be calcined at as low as 350 C in ambient air, the high concentration of thermally decomposed oxygen functional groups (CO/CO 2 /H 2 O) from GO can cause signicant gasication of the ZIF ligand, in the form of CO/CO 2 , [44][45][46] at the expense of the mass yield of the catalyst. Furthermore, owing to the low specic surface area of GO (less than 100 m 2 g À1 ), 44 with its packed layer-structure, it is difficult to achieve a homogeneous hybrid system from the surface grown MOF/ZIF crystals. 30,38,40,47 However, the derivatives of the ZIF@rGO framework with increased surface area can boost the overall activity by facilitating the accessibility and distribution of reactants and products.…”
mentioning
confidence: 99%
See 3 more Smart Citations